The MARVIN Project: A Micrometeorite Harvester in Antarctic Snow - Duprat, J.; Dachwald, B.; Hilchenbach, M.; Engrand, C.; Espe, C.; Feldmann, M.; Francke, G.; Görög, M.; Lüsing, N.; Langenhorst, F. (HAL CCSD, 2013)
International audience MARVIN is an automated drilling and melting probe dedicated to collect pristine interplanetary dust particles (micrometeorites) from central Antarctica snow.